2022
DOI: 10.11157/fohpe.v23i4.579
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in primary medical programs: A scoping review

Abstract: Introduction: Students and universities increasingly seek flexibility in learning options, however terms such as flexible are not consistently defined in the medical education literature. This review aimed to 1) propose a definition for flexibility in medical education and 2) create a typology of contemporary examples of how flexibility has been operationalised in medical education. Method: A systematic scoping review of papers published in English since 2009 was undertaken. The focus was on papers reporting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Student selected components (SSCs) are standard features within UK curricula, providing students with a choice of topics to explore more deeply (Riley, 2009). SSCs are not common in Australasia (Barrett et al, 2022) but could become useful vehicles for faculty to gain confidence in teaching students about key professional challenges. These educational initiatives could then be organised methodically as core material.…”
Section: Addressing Complex Health Issuesmentioning
confidence: 99%
“…Student selected components (SSCs) are standard features within UK curricula, providing students with a choice of topics to explore more deeply (Riley, 2009). SSCs are not common in Australasia (Barrett et al, 2022) but could become useful vehicles for faculty to gain confidence in teaching students about key professional challenges. These educational initiatives could then be organised methodically as core material.…”
Section: Addressing Complex Health Issuesmentioning
confidence: 99%
“…Informed by our scoping review of flexible medical education (Barrett et al, 2022), we surmise that no medical school appears to offer time-flexible study options for the whole course, notwithstanding that a number have options for interrupted, accelerated or decelerated study. Significant minorities of students, 14% in one cohort from the United States reported in an earlier study (Saalwachter et al, 2006), take leave during their course for various reasons, including personal, health or financial reasons, or to complete additional study.…”
Section: Availabilitymentioning
confidence: 99%
“…We are educators at an Australian medical school engaged in curriculum redesign for a time-flexible curriculum and have recently conducted a scoping review on flexible medical education (Barrett et al, 2022). The scoping review found that there are limited examples of time-flexible entry-to-practice medical education.…”
mentioning
confidence: 99%
“…Graduate and postgraduate courses could promote admission of students from diverse undergraduate programs, ensuring that support is available as students enhance their basic clinical sciences. Programs can also enable the intercalation of honours, master's and PhD programs in diverse fields or promote other avenues for individualisation, such as electives and research projects (Barrett et al, 2022).…”
mentioning
confidence: 99%